2017
DOI: 10.1515/prolas-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Sage (Salvia officinalisL.) and Rosemary (Rosmarinus officinalisL.) Essential Oils on Microbiota of Chicken Breast

Abstract: The aim of the study was to evaluate the antimicrobial effect of sage and rosemary essential oils (EO) on microbiota of fresh chicken breast. Sample treatments were stored without packaging, vacuum-packaged, vacuum-packaged with EDTA 1.5% v/w, sage and rosemary EO treatment 0.2% v/w. Assessment of food quality was done by anaerobic plate count (APC), and Enterobacteriaceae, lactic acid bacteria (LAB) and Pseudomonas spp. counts a period of 16 days of storage at 4 ± 0.5 °C. Bacterial species were identified wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Enterobacteriaceae were comprised of Buttiauxella , Enterobacter , Hafnia , Rahnella , Raoultella , and Serratia , with Rahnella aquatis (48%) and Serratia plymuthica (48%) being the most abundant (Table 1). The similar results of the chicken meat after treatment with essential oils were found in a study by Kačániová et al [47].…”
Section: Resultssupporting
confidence: 88%
“…Enterobacteriaceae were comprised of Buttiauxella , Enterobacter , Hafnia , Rahnella , Raoultella , and Serratia , with Rahnella aquatis (48%) and Serratia plymuthica (48%) being the most abundant (Table 1). The similar results of the chicken meat after treatment with essential oils were found in a study by Kačániová et al [47].…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, R2 Italian essential oil showed stronger activity against AChE enzyme compared to other rosemary essential oils previously investigated. Ben Jemia et al [ 20 ] confirmed the neuroprotective activity of S. rosmarinus essential oil from Tunisia. In this study, eight essential oils were screened and the best results were observed for samples collected in Matmata and Dj.…”
Section: Resultsmentioning
confidence: 96%
“…Since the hydrophobicity degree of the active site on the AChE is described to be different among the globular forms of AChE, this may further explain the variation in inhibition seen between studies. In conclusion, the inhibitory activity of the essential oil likely results from a complex interaction of its chemical components, ultimately producing synergistic or antagonistic inhibitory responses [ 20 , 43 ]. Indeed, essential oils are mixtures of components that exhibit generally higher activities than their pure constituents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations